Application of Antifreeze Proteins in Foods of Animal Origin: A Review - Das, Annada; Chauhan, Geeta; Satyaprakash, Kaushik; Tomar, Serlene (International Journal of Livestock Research, 2018)
This paper reviews the origin, functionality and use of antifreeze proteins (AFPs) in frozen foods of animal origin. AFPs inhibit recrystallization and reduce cellular damage, thus safeguarding the quality of frozen foods without structural and organoleptic alterations. The conventional food cryoprotectants are of synthetic/chemical origin and may be hazardous to health. In spite of the limitations like cost and time involvement for small scale purification, the AFPs of natural origin are attracting the interest of researchers for their mass commercial production and application in frozen food. A small amount of purified AFPs are sufﬁcient to exhibit activity without much taste alterations, owing to its commercial benefit. Therefore, naturally occurring AFPs can be used as potent cryopreservatives in frozen meat, fish and dairy products to minimize the structural and functional damages during freezing and thawing.